Realisasi Makna Ideasional dalam Teks Komentator Sepakbola Final Piala AFF 2016 - Sukron Marzuki; Djatmika Djatmika; Sri Marmanto (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2017)
This research attempts to explain the realization of ideational meaning that is used by the commentators of 2016 AFF Cup football match final. The subject is the commentator of 2016 AFF Cup football match final. Meanwhile, the objects of this research are ideational meaning, that is realized in 2016 AFF Cup Final commentator text. The type of this research is descriptive qualitative. The technique that is used is library technique. This research uses functional systemic linguistic as the approach. The lingual data that have been collected are analyzed based on the ideational meaning that involves processes, participants and circumstances. They appear in six types of clauses based on the process (transitivity). There are six type of process to analyze: material process, mental process, verbal process, behavioral process, relational process and existential process. As a result, the commentators most dominantly used material process. Verbal process and mental behavioral process are not found in the commentator text. Keywords: Ideational meaning, processes, participants, circumstance